The effects of apelin on myometrium contractions in pregnant rats - Kacar, Emine; Ercan, Zubeyde; Serhatlioglu, Ihsan; Sumer, Aysegul; Kelestimur, Haluk; Kutlu, Selim (C M B Assoc, 2018)
Apelin, which is a new hormone, is secreted especially in the brain by hypothalamus as well as by many other organs like the stomach, fat tissue, and the heart. For apelin, whose possible effects on many bodily functions like the endocrine system, cardiovascular system and metabolic activities are still under investigation, the reproductive system is also an important target area. The purpose of the present study was to investigate the effects of plasma apelin levels in rats that were in diestrus, pregnancy and lactation periods, and to examine its possible effects on myometrium contractions of pregnant rats and non-pregnant rats that were in diestrus period. The plasma apelin concentrations in female adult Wistar rats were determined with the ELISA method in the diestrus period, and on the 12th, 18th, and 21st days of the pregnancy, and on the 2nd and 10th days of lactation (n=7 for each group). In addition, the effect of apelin at 0.01, 0.1, 1 and 10 mu M doses on isometric contractions in the rat uterus on the 21st day of pregnancy and in diestrus period was tested by using isolated organ bath. This protocol was repeated under conditions that were pre-treated with protein kinase C inhibitor in calcium-free medium, and the possible effect of apelin on contractions and the mechanisms that might mediate this effect were investigated. When plasma apelin levels were compared with the rats in diestrus period, the apelin concentrations in the 21-day pregnancy group were high at a significant level (p<0.05); and low at a significant level in the 2-day lactation group (p<0.05). In myometrium contraction trials, it was observed that apelin induced the contractions. Apelin increased the frequency of the myometrium contractions at a significant level when applied at 1 mu M and 10 mu M concentrations (p<0.05 and p<0.001). Only after the apelin application at 10 mu M concentration did the amplitude of the contractions increase at a significant level (p<0.01). In the myometrium of the rats that were on the 21st day of pregnancy, the frequency of the contractions was statistically significant at 0.1 mu M, 1 mu M and 10 mu M doses (p<0.01). In addition, the amplitude of the contractions increased at a statistically significant level at 1 mu M and 10 mu M dose application (p<0.05 and p<0.01, respectively). The apelin application induced the contractions in calcium-free medium. When apelin was applied after the pre-application with protein kinase C inhibitor, no contractions were observed. The present study showed that apelin levels were increased at the end of pregnancy in rats, and the hormone induced the uterus contractions. This effect does not occur with protein kinase C inhibitor and in calcium-free medium, which shows that protein kinase C pathway might play a role in these mechanism. These findings show that apelin might be an endogenous peptide that plays a role on uterine contractions at birth in rats.
Keywords: Apelin; Contraction; Myometrium; Pregnancy; Tissue Bath